Exploring character education through batik Pekalongan local wisdom: An innovative approach to character learning - Kusnadi, Kusnadi (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
This research investigates the capacity of incorporating indigenous knowledge into the traditional craft of Batik Pekalongan to promote character education and facilitate learning. Batik Pekalongan, an Indonesian textile, is a cultural legacy extending beyond its conventional fabric use. UNESCO has officially designated it as an intangible cultural treasure. The study technique used is a qualitative literature review. The results indicate that including Batik Pekalongan in the curriculum may successfully cultivate robust character attributes in children, including honesty, collaboration, and responsibility. Engaging in partnerships with local batik communities and artists may further enrich students' educational experience via their direct involvement in the batik-making process. This research emphasizes the possibility of using indigenous wisdom in traditional craftsmanship to foster desirable personality qualities and provides a viable alternative to standard character education methods. By integrating indigenous knowledge, education may become more context-specific, pertinent, and efficient in fostering persons with strong moral values and principles.